EFFECT OF MAGNETIC FIELD ON ASPHALT, RESIN, PARAFFIN AND SALT DEPOSITS (Academic journal Industrial Machine Building Civil Engineering, 2017)
The references of studies about the magnetic field effect on prevention of asphalt, resin,and paraffin and salt deposits formation in the oil are described in the article.The effect of constant magnetic fields on the well production is currently one of the mostinteresting, leading to an increase in the overhaul period of the well. At the same time, thismethod is debatable, sometimes leading to ambiguous and contradictory results. In manycases, the nature of such effect is not properly studied. Often, according to some researchers,effect is discovered, whereas its intensity, on the basis of physical considerations, is clearlyinadequate for the production of any useful effect. This refers to the type of magnetic effects,that is based on the principle of protection consisting in a sharp increase in 1000-100000times the number of paraffins crystals nucleus by the action of static magnetic fields oftopology and tension in the natural trace units - rod-shaped mineral oxides / hydroxides ofiron are water, oil and gas production in the flow of production wells.Keywords: development of oil fields, asphalt, paraffins, resins, sediments, asphaltenedeposits, salt deposits, the magnetic field, the magnetic anti-paraffin device.